Assessment of the self-healing capacity of PVA fiber-reinforced composites by chloride permeability and stiffness recovery - Buegger, Urs; Carvalho, Eliane Betania; Jänicke, Ralf; Tofeti Lima, Thamara (Frontiers in Materials, 2024)
This paper investigates the intrinsic ability of PVA fiber-reinforced cementitious composites to re-establish the durability properties of the uncracked state. Comparative chloride penetration tests are used as a direct measure to quantify the effect of self-healing on the chloride penetration resistance after cracking. Two different composites with cement to fly ash ratios of 1:1.5 and 1:2.0 were studied under the influence of healing periods of up to 28 days. After inducing cracks between 100 and 120 μm, samples were exposed to chlorides for 72 h and the resulting chloride penetration depth was compared to the unhealed state. Based on this procedure, a durability recovery index was proposed to quantify the material’s ability to re-establish its function as a protective layer after cracking. Results show that after 14 days of self-healing, chloride penetration through cracks was reduced between 81% and 99%. An extended healing period of 28 days leads to further reduction of the penetration depth to 84%–100%, indicating that most of the reaction takes place within the first 14 days of healing. While the stiffness recovery analysis showed that increasing cement content by 20% correlated with the formation of stronger healing products, no significant difference was found regarding crack closure.